2005
DOI: 10.1080/13506280444000382
|View full text |Cite
|
Sign up to set email alerts
|

Why are moving faces easier to recognize?

Abstract: Previous work has suggested that seeing a famous face move aids the recognition of identity, especially when viewing conditions are degraded (Knight Johnston, 1997; Lander, Christie, Bruce, 1999). Experiment 1 investigated whether the beneficial effects of motion are related to a particular type of facial motion (expressing, talking, or rigid motion). Results showed a significant beneficial effect of both expressive and talking movements, but no advantage for rigid motion, compared with a single static image. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 26 publications
8
73
2
Order By: Relevance
“…The recognition advantage found in these studies is reduced when the precise dynamic characteristic of the observed pattern of motion is disrupted by presenting the frames in a jumbled order or in slow or speeded motion (Lander and Bruce 2000). In addition, the recognition advantage appears only to be present for degraded familiar faces that are rated as having`distinctive', rather than typical, facial movement patterns (Lander and Chuang 2005). Distinctive facial movements are more likely to be idiosyncratic than typical facial movements.…”
Section: (Figure 1)mentioning
confidence: 84%
See 1 more Smart Citation
“…The recognition advantage found in these studies is reduced when the precise dynamic characteristic of the observed pattern of motion is disrupted by presenting the frames in a jumbled order or in slow or speeded motion (Lander and Bruce 2000). In addition, the recognition advantage appears only to be present for degraded familiar faces that are rated as having`distinctive', rather than typical, facial movement patterns (Lander and Chuang 2005). Distinctive facial movements are more likely to be idiosyncratic than typical facial movements.…”
Section: (Figure 1)mentioning
confidence: 84%
“…Distinctive facial movements are more likely to be idiosyncratic than typical facial movements. Taken together, these findings have led researchers to believe that the recognition advantage for recognising degraded dynamic familiar faces appears to be due to the presence of a dynamic facial signature Lander and Chuang 2005).…”
Section: (Figure 1)mentioning
confidence: 99%
“…Others argue that this does not necessarily reflect a true dynamic effect though, and recognition might actually improve because the number of static frames contained within a moving sequence increases (Lander & Chuang, 2005). Lander, Christie and Bruce (1999) have however shown that when the same frames were displayed either as a static array or animated sequence, identity recognition was still significantly higher for the moving sequence.…”
Section: Introductionmentioning
confidence: 99%
“…14). Experiments with famous (i.e., highly familiar) faces [42] again showed a facilitation in recognition with dynamic cues from expressive or talking movements, but not from rigid motion. Facilitation was most pronounced for faces whose movement was judged as Bdistinctive.…”
Section: ) Results 14: Motion Of Faces Appears To Facilitatementioning
confidence: 90%